A Role for Estrogen Receptor Phosphorylation in the Resistance to Tamoxifen - Renée de Leeuw; Jacques Neefjes; Rob Michalides (2011)
About two thirds of all human breast cancer cases are estrogen receptor positive. The drug of first choice for these patients is tamoxifen. However, about half of the recurrences after removal of the primary tumor are or become resistant to this drug. While many mechanisms have been identified for tamoxifen resistance in the lab, at present only a few have been translated to the clinic. This paper highlights the role in tamoxifen resistance of phosphorylation by different kinases on different sites of the estrogen receptor. We will discuss the molecular pathways and kinases that are involved in phosphorylation of ERα and how these affect tamoxifen resistance. Finally, we will elaborate on the clinical translation of these observations and the possibility to predict tamoxifen responses in patient tumor samples before treatment onset. The findings made originally on the bench may translate into a better and personalized treatment of breast cancer patients using an old and safe anticancer drug: tamoxifen.